Factors associated with academic performance of students in music at NCE level: a case study of Oyo state college of education, Oyo, Nigeria (2006)
The study investigates factors associated with music students' academic performance at NCE level using Oyo State College of Education, Oyo, as case study. Purposive sampling procedure was used to administer a questionnaire to all final-year music students. Interview sessions were also held with the educators in the department. The questionnaires were analysed using simple percentage and Spearman's rank correlation method. The result of the statistical analyses showed that students' interest in music, followed by parental influence, correlated with students' performance in music. The outcome of the teachers' interviews revealed the problems of inadequate staffing, poor infrastructure as well as the problem of lack of interest as factors associated with poor academic performance of students. Review of entry requirements as a means of selecting students based on their interest in music, adequate funding, staffing and personnel capacity-building were some of the suggestions made to provide the much-desired enabling environment for learning.